Mechanistic insights into the conformational switch in profilin-1 subject to collective effects of mutation and histidine tautomerism - Muneeswaran, Gurusamy; Lee, Jin Yong (International journal of biological macromolecules, 2023)
Mutations and histidine (His) tautomerism in profilin-1 (PFN1) are associated with amyotrophic lateral sclerosis (ALS). The conformational changes in PFN1 caused by the collective effects of G117V mutation and His tautomeric isomers εε, εδ, δε, and δδ were clarified using molecular dynamics (MD) simulations. The predominant structural variations were seen in α-helices, β-sheets, turns, and coils and the His tautomer's unique degree of disruption was seen in these conformations. The content of α-helices was 23.2 % in the εε and δδ isomers, but the observed α-helices in the isomers εδ and δε were 20.3 % and 21.7 % respectively. The percentage of β-sheet was found to be higher (34.1) in the εε isomer than in the εδ, δε, and δδ isomers, and the values were 30.4, 29.7, and 31.9, respectively. Intermolecular water dynamics analysis discloses that His 133 can form an intramolecular H-bond interaction (Nα-H---Nδ), confirming the experimental observations in the simulations of εε, δε, and δδ isomers of G117V PFN1 mutant. It was concluded that these solvent molecules are crucial for aggregation and must be considered in future research on the PFN1 associated with ALS. Overall, the study offers a thorough microscopic understanding of the pathogenic mechanisms behind conformational changes that cause aggregation illnesses like ALS.